Easter Week Visit to Albert Watkins and Rose Watkins in Huntington Beach - Watkins, Howard::::::::: (1984)
Bertha Watkins, Aaron "Jack" Watkins, Howard Watkins, Albert Watkins, Adam Watkins, Rose Watkins holding Robin Watkins on her lap